Pengaruh Lingkungan Kerja Dan Keselamatan Kerja Terhadap Kinerja Karyawan Bagian Produksi Pada Pt. Sari Warna Asli Unit Ii Boyolali - Sawab, Dewi Nurhayati; , Ahmad Mardalis, S.E. M.B.A (2015)
Goals to be achieved in the implementation of this research are: (1) To analyze the effect of the work environment on the performance of employees of PT. Sari Warna Asli Unit II Boyolali. (2) To analyze the impact of safety on the performance of employees of PT. Sari Warna Asli Unit II Boyolali. (3) To analyze the influence of the working environment and safety on the performance of employees of PT. Sari Warna Asli Unit II Boyolali. The technique of collecting data using questionnaires, observation, literature study and documentation study. The population in this study were all employees of the production of PT. Sari Warna Asli Unit II Boyolali amounting to 236 people. The sampling method using incidential sampling and sample set as many as 70 people. Test instrument used in this study is to test the validity and reliability. Then performed classical assumption in the form of normality test and multicollinearity. Multiple linear analysis methods used by F test, T test, and coefficient of determination. The results showed that the classical assumption is not found problems. T test results showed that there is positive and significant correlation between the work environment on employee performance. This shows that if the working environment is getting better, then the employee's performance will increase. There is positive and significant correlation between safety on employee performance. This shows if the level of safety is higher, then the employee's performance will increase as well. At f test showed that jointly (simultaneously) variable working environment and safety at work and significant positive effect on employee performance. Results obtained coefficient of determination (R2) of 30.8%.